Analysis Of Iri And Sdi Methods As A Basis For Determining Road Functional Conditions - Octavia, Syarifah Nur; Yulistiyanti, Liana Dwi; Setyanta, Nunuk Chandra; Wicaksono, Reza Husain; Setyobudi, Risang (Universitas Teuku Umar, 2024)
Assessment lof lroad lconditions lneeds lto lbe ldone lperiodically las la lreference lin ldetermining levaluation lof lfunctional lroad lconditions. lThe lparameters lrelated lto lfunctional lconditions lare lthe llevel lof lroughness, las lwell las lthe lactual llevel lof ldamage lin lthe lfield lsuch las larea, lcrack lwidth, lnumber lof lholes land lthe ldepth lof lthe lgrooves lof lthe lruts. lBased lon lthe lproblems lmentioned labove, lit lis lnecessary lto lanalyze lthe lfunctional lcondition lof lthe lroad lusing lIRI land lSDI lvalues las lwell las lthe lcalculation lof lthe lconstruction lcost lbudget lon lthe lpakah l- lpucangan l- lgesikharjo lroad lsection.Setiawan, lPradani land lMasoso l(2019) largued lthat l